Prediction of Compounds from 96% Ethanol Extract of Marsilea crenata Presl. Leaves in Increasing Estrogen Receptor-α Activation - Ma’arif, Burhan; Muslikh, Faisal Akhmal; Fihuda, Destiya Argo Pamuji; Syarifuddin, Sadli; Fauziyah, Begum (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2021)
Women who experience menopause will experience estrogen deficiency, which will impact their health, one of which will increase the risk of neurodegenerative. Phytoestrogen compounds in Marsilea crenata can provide activity after binding to their receptors or ER-dependent pathways. The research was conducted in silico with the molecular docking method using the ERα (1A52) receptor. In silico analysis was carried out on the metabolite profiling compound of the 96% ethanol extract of M. crenata leaves from the previous study. Sample preparation was carried out using the Biovia Discovery Studio 2021 application to separate macromolecules and native ligands and prepared to get a 3D structure using ChemDraw Ultra 12.0. then analyzed its pharmacokinetics and pharmacodynamics with the SwissADME webtool. Furthermore, the geometry of the compound was optimized using Avogadro 1.0.1, and molecular docking of the compound to the 1A52 receptor was carried out using Autodock vina (PyRx 0.8). The interaction visualization stage was carried out with Biovia Discovery Studio 2021, and a toxicity test was carried out using the ProTox II online tool. The results of the in-silico study showed that six compounds met the pharmacokinetic and pharmacodynamic criteria, toxicity, and had similar pharmacophore distances and amino acid binding with native 17β-estradiol, a 1A52 agonist with anti-neuroinflammatory effect. So, 96% ethanol extract of M. crenata leaves is predicted to potentially inhibit PD progression with an anti-neuroinflammatory mechanism.